2005
DOI: 10.1086/427663
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin‐Binding Proteins and Fibrinogen‐Binding Clumping Factors Play Distinct Roles in Staphylococcal Arthritis and Systemic Inflammation

Abstract: Staphylococcus aureus is a commonly encountered pathogen in humans, and it has the potential to cause destructive and life-threatening conditions, including septic arthritis. The pathogenicity of staphylococci depends on the expression of virulence factors. Among these, staphylococcal cell-surface proteins with tissue-adhesive functions have been suggested to mediate the colonization of host tissues, a crucial step in the establishment of infection. We investigated the relative contribution of the fibronectin-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 58 publications
1
47
1
Order By: Relevance
“…In addition, five other adhesin mutants showed a similarly reduced ability (52-65 % attachment) to bind C. albicans, although these differences were not statistically significant due to larger SD. The creation of single, double, triple, or octuple mutants in these adhesins has been shown to eliminate the ability of S. aureus to both form biofilms and survive in vivo (Bose et al, 2012;Chen et al, 2013;Kenny et al, 2009;Mazmanian et al, 2000;Palmqvist et al, 2005). Therefore, these S. aureus mutants are no longer able to systemically spread in cases of co-infection with C. albicans regardless of the mechanism of deep tissue delivery.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, five other adhesin mutants showed a similarly reduced ability (52-65 % attachment) to bind C. albicans, although these differences were not statistically significant due to larger SD. The creation of single, double, triple, or octuple mutants in these adhesins has been shown to eliminate the ability of S. aureus to both form biofilms and survive in vivo (Bose et al, 2012;Chen et al, 2013;Kenny et al, 2009;Mazmanian et al, 2000;Palmqvist et al, 2005). Therefore, these S. aureus mutants are no longer able to systemically spread in cases of co-infection with C. albicans regardless of the mechanism of deep tissue delivery.…”
Section: Resultsmentioning
confidence: 99%
“…AT is a secreted pore-forming toxin (34) found to promote biofilm formation in vitro (35,36) and to contribute to immune evasion in a murine model of orthopedic implant infection (37). ClfA is a surface-expressed fibrinogen-binding adhesin that has been shown to promote biofilm-like aggregations in synovial fluid (38) [providing a role for ClfA in septic arthritis (39,40)] and is highly expressed in human orthopedic implant infections (41). The anti-AT and anti-ClfA mAbs (0.5 μg/mL each) were first determined to have no effect, either alone or in combination, on the planktonic growth of NRS384 in broth culture (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, high production of IL-6 in wild-type strain-or fnbB mutant-infected mice should be one of the major causes of significant alteration of body weight, unhealthy appearance, and drastic lethality. Palmqvist et al also demonstrated the contribution of FnBPs to systemic infection (40). They compared the pathogenicity of wild-type S. aureus strain LS-1 with its mutant lacking both fnbA and fnbB and demonstrated that the fnbA fnbB mutant caused no change in the body weights of mice and lower production of serum IL-6 than the wild-type strain.…”
Section: Vol 79 2011 Role Of Fnbps In S Aureus Infection 2217mentioning
confidence: 99%